Proceedings of the 51st Annual ACM SIGACT Symposium on Theory of Computing 2019
DOI: 10.1145/3313276.3316336
|View full text |Cite
|
Sign up to set email alerts
|

The structure of optimal private tests for simple hypotheses

Abstract: Hypothesis testing plays a central role in statistical inference, and is used in many settings where privacy concerns are paramount. This work answers a basic question about privately testing simple hypotheses: given two distributions P and Q, and a privacy level ε, how many i.i.d. samples are needed to distinguish P from Q subject to ε-differential privacy, and what sort of tests have optimal sample complexity? Specifically, we characterize this sample complexity up to constant factors in terms of the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…However, Brenner and Nissim (2014) showed that when the data are non-binary, there is no universal utility maximizing mechanism such as the staircase mechanism. As Canonne et al (2018) discuss, this result seems to imply that in settings where the data is non-binary, it may not be possible to develop DP-UMP tests.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Brenner and Nissim (2014) showed that when the data are non-binary, there is no universal utility maximizing mechanism such as the staircase mechanism. As Canonne et al (2018) discuss, this result seems to imply that in settings where the data is non-binary, it may not be possible to develop DP-UMP tests.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Following a common strategy in the field of Statistics, Wang et al (2018) develop approximating distributions for DP statistics, which can be used to construct hypothesis tests and confidence intervals. In a recent work, Canonne et al (2018) show that for simple hypothesis tests, a DP test based on a clamped likelihood ratio test achieves optimal sample complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Canonne et al [ 52 ] calculated the sample complexity bounds of an ε -differentially private test for distinguishing between two distributions. They also applied differentially private change-point detection.…”
Section: Related Workmentioning
confidence: 99%
“…The maximal-leakage setting inverts this goal, and protects the observed values while maximizing the detection of hypotheses on the distributions. This distinction in goal also applies with respect to the distributional privacy framework [2] and in the explorations of [3] into general privatized hypothesis testing.…”
Section: Related Work and Related Privacy Definitionsmentioning
confidence: 99%